"I think deprescribing is very needed in our society:" Healthcare Professional Students Perceptions of Deprescribing Education - Alina Cernasev; Devin Scott; Rachel Barenie; Crystal Walker; Muneeza Khan; William Callahan; Amy Hall (University of Minnesota Libraries Publishing, 2024)
Introduction: Deprescribing is a complex and pivotal process in the healthcare system that requires the involvement of different healthcare professionals as well as patients and family members. Given the multifaceted healthcare professionals involved in deprescribing, fostering interdisciplinary healthcare teams during the didactic and experiential educational engagement is imperative. Thus, this study aimed to to characterize healthcare professional students' opinions on the importance of an interdisciplinary approach to deprescribing during the didactic and experiential components of the curriculum. Methods:This qualitative study was conducted with healthcare professional students enrolled in a professional degree program at one Mid-South health science located in the US. Focus groups were conducted via an online platform over three months in 2022, and recruitment continued until thematic saturation was achieved.Using Thematic Analysis, the corpus of the transcribed data was imported into the Dedoose®, a qualitative software that facilitated the analysis. Results: A total of 36 healthcare professional students participated in four focus groups.  Three themes emerged from the data: 1) setting the stage for deprescribing, 2) developing interprofessional deprescribing simulations, 3) potential positive patient outcomes. In the first theme, the healthcare professional students describe current challenges in the deprescribing process that call attention to the interprofessional nature of deprescribing. The second theme demonstrates the necessity of developing interprofessional simulations to educate healthcare professional students in the practice of deprescribing. Finally, in the third theme, the healthcare professional students illustrate the potential of interprofessional education on deprescribing to improve patient outcomes. Conclusion:The data highlights that there was strong agreement between extant literature and health professions participants on barriers to deprescribing, including interprofessional communication issues, and on the recommendation to enact interprofessional healthcare simulation education on deprescribing. In addition, the potential benefits of increased interprofessional education will provide immeasurable benefits and create an ample understanding of the roles of health professionals. These findings suggest that deprescribing focused interprofessional healthcare simulation educational activities should be conducted and assessed.